Predicción de la quiebra en las empresas. Una revisión de literatura (2021)
The current environment in which companies operate worldwide involves a wide range of risks that can lead companies to declare bankruptcy and disappear. It is essential to somehow be able to foresee these types of circumstances, which is why many authors have addressed this issue with different results. This paper reviews the existing literature on business bankruptcy over a 68-year period (1950-2017), a time period that involved an analysis of 4,439 papers published using techniques such as keyword concurrency analysis and citation networks. This extensive review allowed the identification of two clear research trends in this regard: the first, related to the financial structure of companies and debt; the second, around publications related to techniques, methods, and statistical aspects of business bankruptcy prediction.